FORGIVENESS AS REFLECTED IN FRANCINE RIVERS’ REDEEMING LOVE MOVIE - Sumala, Novella; Tuerah, Ignatius J. C.; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study was carried out to reveal the forgiveness and its impacts in Francine Rivers’ Redeeming Love Movie. The writer delimited this study on forgiveness experienced throughout the main characters in the movie namely Angel and Michael.  This research used qualitative research design because the data were in the form of quotation or description.  In carrying out this research, the data were obtained from the movie entitled Redeeming Love as primary source and also supported by other relevant references such as books, documents and other sources about forgiveness were considered as secondary sources.  The result of the study described that Angel went through a process of self-awareness and acceptance, recognizing that they are not defined by their past mistakes. The novel underscores the theme of redemption and second chances through forgiveness. Transformative power of unconditional love is illustarated and seen in the character of Michael. Characters actively decide to forgive, demonstrating that forgiveness is not a passive process but a conscious decision made by individuals who seek healing and restoration in their relationships. Forgiveness serves as a powerful tool for promoting healing, reconciliation, and personal transformation in various contexts, both in general and special.